Assessment of Cross-correlations Between Selected Macromolecules in Urine of Children with Idiopathic Hypercalciuria - Jobs, Katarzyna; Jung, Anna; Lewicki, Slawomir; Murawski, Piotr; Paczek, Leszek; Zdanowski, Robert (Urology Journal, 2018)
Purpose: The aim of the study was assessment of four selected macromolecules level: osteopontin, calgranulin, uromodulin and bikunin in fresh morning urine sample in children with nephrolithiasis in the course of idiopathic hypercalciuria. Materials and Methods: The study included 90 subjects aged from 12 months to 18 years. The study group comprised 57 subjects- children with urinary tract lithiasis in the course of idiopathic hypercalciuria and the control group - 33 healthy children with no history of urolithiasis. Determinations of osteopontin, calgranulin, uromodulin and bikunin levels in the first morning urine were performed. Results: The study group had a significantly decreased osteopontin excretion and significantly increased bikunin excretion, and increased, however statistically nonsignificant, calgranulin excretion in comparison with the control group. Uromodulin excretion did not differ between groups. In both groups a statistically significant positive correlation was observed between uromodulin and bikunin levels. Conclusion: Children with urinary tract lithiasis in the course of idiopathic hypercalciuria reveal a different distribution of the study proteins than a healthy population.